2005
DOI: 10.1007/s00702-005-0303-7
|View full text |Cite
|
Sign up to set email alerts
|

Activation of glycogen synthase kinase-3 induces Alzheimer-like tau hyperphosphorylation in rat hippocampus slices in culture

Abstract: Formation of neurofibrillary tangle from hyperphosphorylated tau is one of the hallmark lesions seen in Alzheimer's disease (AD) brain, and neuronal deregulation of glycogen synthase kinase-3 (GSK-3) activity plays key role in tau hyperphosphorylation. In the present study, the role of GSK-3 on tau phosphorylation in hippocampus slice culture was examined by incubating the slice with wortmannin (WT), an inhibitor of phosphatidylinositol 3-kinase (PI3K) and GF-109203X (GFX), an inhibitor of protein kinase C (PK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 32 publications
4
49
0
3
Order By: Relevance
“…To date, several studies have shown that the Wnt signaling components b-catenin and GSK3b form multiprotein complexes with the early-onset familial AD-linked presenilin proteins (Zhou et al, 1997;Takashima et al, 1998b;Kang et al, 2002). b-Catenin levels are significantly reduced in AD individuals bearing presenilin mutations (Zhang et al, 1998) and active GSK3b accumulates in vivo in AD brains (Pei et al, 1999), where it has a key role in the hyperphosphorylation of the microtubule-associated protein tau (Hanger et al, 1992;Lovestone et al, 1994;Lucas et al, 2001;Sato et al, 2002;Li et al, 2006). Moreover, Wnt signaling may also have an essential role in the processing of the amyloid precursor protein (Mudher et al, 2001;Sun et al, 2002;Phiel et al, 2003), as well as in the neurotoxicity of its derivative the amyloid b-peptide (Ab) (Takashima et al, 1998a;Alvarez et al, 2002;De Ferrari et al, 2003;Alvarez et al, 2004;Caricasole et al, 2004).…”
Section: Alzheimer's Disease Apolipoprotein E and Wnt Signalingmentioning
confidence: 99%
“…To date, several studies have shown that the Wnt signaling components b-catenin and GSK3b form multiprotein complexes with the early-onset familial AD-linked presenilin proteins (Zhou et al, 1997;Takashima et al, 1998b;Kang et al, 2002). b-Catenin levels are significantly reduced in AD individuals bearing presenilin mutations (Zhang et al, 1998) and active GSK3b accumulates in vivo in AD brains (Pei et al, 1999), where it has a key role in the hyperphosphorylation of the microtubule-associated protein tau (Hanger et al, 1992;Lovestone et al, 1994;Lucas et al, 2001;Sato et al, 2002;Li et al, 2006). Moreover, Wnt signaling may also have an essential role in the processing of the amyloid precursor protein (Mudher et al, 2001;Sun et al, 2002;Phiel et al, 2003), as well as in the neurotoxicity of its derivative the amyloid b-peptide (Ab) (Takashima et al, 1998a;Alvarez et al, 2002;De Ferrari et al, 2003;Alvarez et al, 2004;Caricasole et al, 2004).…”
Section: Alzheimer's Disease Apolipoprotein E and Wnt Signalingmentioning
confidence: 99%
“…Tau hyperphosphorylation at site Ser 199 is directly linked with AD. 32) Our study found that tau phosphorylation increased in a high glucose environment, but that ghrelin attenuated this change. Ghrelin improved insulin-stimulated neuronal tau phosphorylation (Fig.…”
Section: Discussionmentioning
confidence: 45%
“…Much evidence has suggested that GSK-3β is physically complexed with tau in the brain and phosphorylates tau in vitro and in vivo [14,15], and plays an important role on the phosphorylation of tau through the activation of phosphatidylinositol 3-kinase (PI3K) [16,17]. To clarify the role of leptin signaling on the activation of Akt and GSK-3β, we determined the effects of LA on the phosphorylation of Akt at ser-473 site and GSK-3β at ser-9 site in rat primary cultured cortical neurons.…”
Section: Effect Of Leptin Signaling On Geniposide-regulated Gsk-3β Anmentioning
confidence: 99%